Evaluation of the disinfectant “Enzidez” according to indicators of acute toxicity and irritant effect - V. Kozhyn; V. Salata; M. Kukhtyn; O. Vasylkiv; S. Laiter-Moskaliuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Despite the fairly large number of disinfectants on the market, there is no perfect drug, as microorganisms adapt to new antibacterial substances quite quickly. In this regard, recently, enzymatic preparations for the hydrolysis of protein contaminants and the destruction of the glycopeptide matrix of the microbial biofilm have been introduced into disinfectants. Therefore, disinfectants that have a wide spectrum of antimicrobial action, actively remove organic contaminants and affect the biofilm forms of bacteria are considered relevant and promising for development. The purpose of the work was to conduct a toxicological evaluation of the developed disinfectant “Enzidez” according to indicators of acute toxicity and irritant effect. Determination of acute toxicity and irritant effect of the native disinfectant and its 1 % solution was carried out according to generally accepted methods. Studies on establishing the parameters of subacute (acute) toxicity of Enzidez disinfectant on white mice revealed that the working 1.0 % concentration of Enzidez disinfectant did not cause the death of mice when administered intragastrically in a dose of 5000 to 13000 mg/kg. This indicates that a dose of 13,000 mg/kg body weight will be tolerated (LD0) for animals, while the median lethal (LD50) dose will be higher than this amount. According to the classification regarding the harmfulness of substances, the disinfectant in a working concentration of 1.0 % will be considered low-toxic (toxicity class 4).In the pathological autopsy of laboratory mice after administering lethal and working doses of the drug “Enzidez” to them, it was established that the mice died from pulmonary insufficiency due to hyperemia and pulmonary edema. According to the degree of danger, the product belongs to class 4 (low-toxic substances). When a working 1.0 % solution of the disinfectant was injected into the stomach, no visible pathological-anatomical changes were detected in experimental mice after euthanasia, which indicates its low toxicity. In addition, it was found that the native solution of the disinfectant causes slight irritation to the skin of white rabbits, so rubber gloves should be used when preparing working concentrations of the solution. The working 1 % solution of Enzidez, in turn, did not cause an irritating effect. In addition, it was found that the native solution of the disinfectant caused a harmful effect of 9 points on the mucous membrane of the eyes, and the working – 1 % solution did not cause visible changes in the mucous membrane. Therefore, when working with the native disinfectant “Enzidez”, it is necessary to use eye protection – glasses.